ANALISIS KUALITAS HASIL GAMBAR SEQUENCE T1 FAT SAT DAN SPECTRAL ADIABATIC INVERSION RECOVERY (SPAIR) PADA POTONGAN SAGITAL MRI PELVIS DENGAN KLINIS ENDOMETRIOSIS - Mawarsari, Septi (JRI (Jurnal Radiografer Indonesia), 2020)
Background : Examination of women's pelvis with clinical endometriosis using sequence T1 fat sat with the reason in the description of T1 fat sat will increase the contrast of the filling, see the difference between tissues containing fat and not, increase the sensitiveness in detecting small endometriosis and help distinguish it from cysts. SPAIR is a very powerful technique for fat suppression, which gives different advantages compared to conventional fat suppression techniques. MRI examination of pelvic endometriosis on sagittal pieces using SPAIR is unlike in theory that more recommend T1 fat sat. Because of the sequence differences, the authors were interested to examine more about the quality of the picture results with the sequence of T1 fat sat and SPAIR on the partal pieces of MRI Pelvic endometriosis. Method : Design This research is quantitative analytics with observation methods, experiments and questionnaires. Conducted at the MRI Installation of Fatmawati Central General Hospital in February 2016 to May 2016 with a study sample of 10 patients using primary data. T1 Fat Sat and SPAIR overviews are qualitatively analyzed using questionnaires based on the assessment of radiology specialists and radiographers by assessing diagnostic information in terms of anatomy, resolution, contrast and noise. Data analysis is done using Independent T test. Result : The result of this study is to show a 'significant difference in anatomy, resolution and contrast characterized by the value p value = 0.000 (p < 0.05) while in the noise there is no significant difference marked by p value = 0.065 (p > 0.05).